2017
DOI: 10.1186/s12877-017-0586-1
|View full text |Cite
|
Sign up to set email alerts
|

Latent class analysis of multimorbidity patterns and associated outcomes in Spanish older adults: a prospective cohort study

Abstract: BackgroundThis study sought to identify multimorbidity patterns and determine the association between these latent classes with several outcomes, including health, functioning, disability, quality of life and use of services, at baseline and after 3 years of follow-up.MethodsWe analyzed data from a representative Spanish cohort of 3541 non-institutionalized people aged 50 years old and over. Measures were taken at baseline and after 3 years of follow-up. Latent Class Analysis (LCA) was conducted using eleven c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

21
83
4
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(120 citation statements)
references
References 58 publications
21
83
4
6
Order By: Relevance
“…Guisando‐Clavero et al use cluster analysis to identify six patterns of comorbidities in a study of 190 108 patients with multimorbidities. Several other researchers perform either cluster analysis or Latent Class Analysis (LCA, or exploratory factor analysis [EFA]) to identify patterns of multimorbidity . EFA and LCA are dimensionality reduction methods that collapse combinations of observed variables into unobserved factors.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Guisando‐Clavero et al use cluster analysis to identify six patterns of comorbidities in a study of 190 108 patients with multimorbidities. Several other researchers perform either cluster analysis or Latent Class Analysis (LCA, or exploratory factor analysis [EFA]) to identify patterns of multimorbidity . EFA and LCA are dimensionality reduction methods that collapse combinations of observed variables into unobserved factors.…”
Section: Methodsmentioning
confidence: 99%
“…Class Analysis (LCA, or exploratory factor analysis [EFA]) to identify patterns of multimorbidity. [21][22][23][24][25] EFA and LCA are dimensionality reduction methods that collapse combinations of observed variables into unobserved factors. These factors can then be used to represent subgroups.…”
Section: Several Other Researchers Perform Either Cluster Analysis Ormentioning
confidence: 99%
“…A handful of studies have investigated multimorbidity patterns and their relationship with healthcare outcomes. [21][22][23][24] Olaya et al (2017) found two multimorbid patternsthe cardiovascular/mental/arthritis and the metabolic/strokethat were significantly associated with more use of health services. 21 Another study found four multimorbid patterns: Heart impairment, Metabolic-ischemic, Cardio-respiratory, and Cancer were associated with hospitalization.…”
Section: Introductionmentioning
confidence: 99%
“…En este sentido, Nariño ocupa el segundo lugar en cuanto a víctimas de conflicto armado en Colombia(27). En relación con el desempeño funcional de los adultos mayores indígenas, se pudo evidenciar que la gran mayoría son funcionales en las actividades básicas e instrumentales de la vida diaria, lo anterior posiblemente alude a la particularidad de su contexto, en el que se hacen prácticas de trabajo comunitario y siempre existirá la actividad física que, de alguna manera, refuerza su potencial o capacidad de desempeño para la autonomía y la independencia(28).De manera similar, a partir los hallazgos del perfil de salud derivado del acl, se pudieron establecer tres grandes grupos. En primer lugar, las clases 1 y 3, compuestas por individuos con una alta presencia de comorbilidad, riesgo de desnutrición, deterioro cognitivo y sintomatología depresiva.…”
unclassified
“…Por otro lado, en menos del 5 % de los adultos mayores que pertenecen a la clase 3 se presentó baja comorbilidad y mayor presencia de riesgo de desnutrición. La clase 2 muestra un perfil de salud más favorable, aunque los individuos de esta clase presentan riesgos de desnutrición.Un estudio reciente realizado en adultos mayores de población general no indígena muestra hallazgos similares, aunque menos desfavorables(28).En este estudio al que aludimos se encontraron tres clases. Dos terceras partes de los adultos mayores fueron clasificados en la clase "saludable", una tercera parte en la clase…”
unclassified